52 THE INFLUENCE OF EXTRACELLULAR ACIDOSIS ON THE EFFECT OF ANTI-ARRHYTHMIC AGENTS ON THE CARDIAC POTASSIUM CHANNEL (IKr). (1st March 2005) - Lin, C.; Ke, X.; Cvetanovic, I.; Ranade, V.; Somberg, J. C.
Abstract : Objectives: Major pH changes can take place during ischemia and reperfusion, and the resulting acidosis could result in arrhythmias. The human-ether-a-go-go-related gene (HERG) encodes the rapid component of delayed rectifier potassium current (IKr), which is critical for cardiac repolarizartion. We evaluated the effect of extracellular pH on the IKr inhibition caused by amiodarone, azimilide, dofetilide, and quinidine. Methods: IKr was studied at room temperature by using HERG gene expressed in Xenopus oocytes and two electrodes voltage clamp technique. Results: Extracellular acidification decreased the amplitudes of the outward current and the large tail outward current, while the decay of tail current was accelerated. The steady state current was decreased by 14.4 ± 6.8%, 19.8 ± 10.4%, 23.8 ± 10.4%, 28.3 ± 10.5%, and the tail current was decreased by 6.7 ± 1.1%, 8.7 ± 2.1%, 13.4 ± 1.5%, and 26.4 ± 3.0% when decreasing pH from 8.0 to 7.4, 7.0, 6.6, and 6.2, respectively. Acidification and IKr blocking drugs (quinidine, dofetilide, azimilide and amiodarone) were also studied. There was no additive or synergistic effect between extracellular H+ and drugs on HERG channels. Quinidine 10 μM inhibited HERG tail current by 37.2 ± 4.8% at pH 7.4. This inhibition was increased to 50.9 ± 4.7% when extracellular pH was 8.0 and decreased to 4.5 ± 1.8% when pH was 6.2. Dofetilide 0.3 μM inhibited HERG tail current by 64.4 ± 7.4, 33.5 ± 2.6, and 1.4 ± 2.4% at pH 8.0, 7.4, and 6.2 respectively. Azimilide 10 μM inhibited HERG tail current by 63.0 ± 3.6, 58.7 ± 2.9, and 17.4 ± 3.2% at pH 8.0, 7.4, and 6.2 respectively. One way ANOVA test showed that there was a significant difference in current block among the different pH groups. The IC50 was 5.8 ± 0.3 μM for azimilide, 9.9 ± 1.01 μM for quinidine, and 0.5 ± 0.02 μM for dofetilide. When pH was decreased from 7.4 to 6.2, the IC50 increased to 95 ± 11 μM for azimilide, 203 ± 16 μM for quinidine, and 13 ± 1 μM for dofetilide. For amiodarone, the IC50 was 38 ± 9 μM at pH 7.4 and 27 ± 2 μM at pH 6.2. There was no significant difference in the percentage current block by amiodarone between pH 6.2 and 7.4. The block was minimally changed (1%) by amiodarone when pH decreased from 7.4 to 6.2. Conclusion: The IKr blocking effect of azimilide, dofetilide, and quinidine was attenuated at acidic pH while this was not the case for amiodarone. The effect of azimilide, dofetilide, and quinidine at low pH creates heterogeneity of repolarization between ischemic and normal regions, but this is not the case with amiodarone. These observations may explain the reduced proarrhythmia seen with amiodarone clinically.